Ectodermal Organ Development Is Regulated by a microRNA-26b-Lef-1-Wnt Signaling Axis - Eliason, Steve; Sharp, Thad; Sweat, Mason; Sweat, Yan Y.; Amendt, Brad A. (Frontiers in Physiology, 2020)
The developmental role of Lef-1 in ectodermal organs has been characterized using Lef-1 murine knockout models. We generated a Lef-1 conditional over-expression (COEL) mouse to determine the role of Lef-1 expression in epithelial structures at later stages of development after endogenous expression switches to the mesenchyme. Lef-1 over expression (OE) in the oral epithelium creates a new dental epithelial stem cell niche that significantly increases incisor growth. These data indicate that Lef-1 expression is switched off in the dental epithelial at early stages to maintain the stem cell niche and regulate incisor growth. Bioinformatics analyses indicated that miR-26b expression increased coinciding with decreased Lef-1 expression in the dental epithelium. We generated a murine model over-expressing miR-26b that targets endogenous Lef-1 expression and Lef-1-related developmental mechanisms. miR-26b OE mice have ectodermal organ defects including a lack of incisors, molars and hair similar to the Lef-1 null mice. miR-26b OE rescues the Lef-1 OE phenotype demonstrating a critical genetic and developmental role for miR-26b in the temporal and spatial expression of Lef-1 in epithelial tissues. Lef-1 expression regulates Wnt signaling and Wnt target genes as well as cell proliferation mechanisms, while miR-26b OE reduced the levels of Wnt target gene expression. The extra stem cell compartment in the COEL mice expressed Lef-1 suggesting that Lef-1 is a stem cell factor, which was absent in the miR-26b OE/COEL rescue mice. This is the first demonstration of a microRNA OE mouse model that has ectodermal organ defects. These findings demonstrate that the levels of Lef-1 are critical for development and establish a role for miR-26b in the regulation of ectodermal organ development through the control of Lef-1 expression and an endogenous stem cell niche.